THE PHYSICAL CHARACTERISTIC TEST OF GAMAL (Gliricidia sepium) PELLET THAT ADDED OF BINDER - Royani, Mega; Herawati, Ervi (Universitas Djuanda Bogor, 2020)
The experiment was conducted to study the influence of binder on physical characteristic Gamal pellet. The data were anlyzed by analyzed of variance and significant experiment result would be examined by Duncan’s Multiple Range Test. The treatments were consisted of P1 (30% molasses+ 70% Gamal meal), P2 (40% molasses + 60% Gamal meal), P3 (30% Tapioca + 70% Gamal meal), P4 (40% tapioca + 60% Gamal meal) and P5 (20% tapioca + 20% molasses + 60% Gamal meal). Variabel measured were spesific gravity, bulk density and compacted bulk density. The resuls showed that the treatment had significant effect (P> 0.05)on spesific gravity and bulk density but did not had significant effect (P<0,05) on compacted bulk density. The conclusion of the experiment that added of 30% molasses (P1) as binder gave the optimum physical characteristic of Gliricidia sepium pellet.Keywords : Binder, Physical characteristic test,Gamal Pellet